Organic bistable memory devices utilizing PMMA polymer matrix-based ZnOsingle bondC60 core-shell QDs nanocomposites - Shim, Jaeho; Park, Jinseo; Seo, Seok Ho; You, Ju Hee; Son, Dong Ick (Elsevier, 2025)
This study explores the development of organic bistable memory devices (OBMDs) leveraging ZnO-fullerene (C60) core-shell QDs embedded within a poly(methyl methacrylate) (PMMA) polymer matrix. Employing a spin-coating methodology, ZnO QDs were encapsulated with fullerene C60, a molecule renowned for its high electron affinity, to establish a robust core-shell configuration. This design significantly enhanced quantum confinement and provided efficient charge trapping capabilities. Structural analyses using transmission electron microscopy (TEM) confirmed the uniform dispersion and precise formation of ZnOsingle bondC60 QDs, exhibiting an average particle size of approximately 10 nm within the polymer matrix. The electrical performance of Al/ZnOsingle bondC60 QD-embedded PMMA/ITO devices was evaluated at 300 K, revealing clear bistable characteristics. The devices achieved a high ON/OFF current ratio of 7.46 × 103, demonstrated exceptional cycling endurance exceeding 1.5 × 104 cycles, and exhibited long-term retention surpassing 1.2 × 105 s. Detailed analysis of current-voltage (I-V) data highlighted Fowler-Nordheim (F-N) tunneling as a key mechanism facilitating efficient memory operation. These findings underscore the potential of ZnOsingle bondC60 core-shell QDs as a transformative material system for advanced non-volatile memory technologies. This work provides a foundation for further exploration into scalable and energy-efficient memory devices suitable for next-generation electronics and optoelectronics.